The impacts of tourism development on poverty alleviation in Sarawak - Rossazana, Ab. Rahim; Komathi, Wasudawan (Universiti Malaysia Sarawak (UNIMAS), 2017)
The study aims to investigate economic impact of tourism development such as local economy development, tourism entrepreneurial activity and tourism employment generation in alleviating poverty. Five hundred and twenty local community from Kuching and Miri, East Sarawak, Malaysia have participated in the research. The result indicates that the tourism development contributes to the local economy development, creates tourism entrepreneurial activity and generates tourism employment among the local communities’ in increasing the household income.